Overshoot-free acceleration of aero-engines: An energy-based switching control method. (February 2016) - Wang, Xia; Zhao, Jun; Sun, Xi-Ming
Abstract: A switched controller is proposed for a two-spool turbofan engine to achieve overshoot-free speed control. Instead of a mathematical engine model, the real time data provided by the component level model and the equilibrium manifold are used in the design process. Controllers and a switching law are proposed to ensure that the system energy will not surpass the energy of the target working point so that no speed overshoot will arise. Meanwhile, the engine works at its safety limits as much as possible during the acceleration process, which shortens the regulation time. The asymptotic regulation, the overshoot-free performance as well as the safety issues are guaranteed theoretically. Simulations of a two-spool turbofan engine testify the correctness of the proposed method.